Prevalence and risk factors associated with Fasciola gigantica and Paramphistomum cervi infection through actual retrieval in Philippine Carabaos in Ormoc City Abattoir, Philippines - Lumain, John Philip Lou M.; Balala, Lotis M. (Annals of Tropical Research, 2019)
This study determine the prevalence and risk factors associated with Fasciola and Paramphistomum and the co-infection of both parasites in 246 Philippine carabaos slaughtered in Ormoc City abattoir. Upon postmortem examination, adult parasites were collected from the organ of localization and identified based on morphological characteristics. Intrinsic factors [sex, age, weight, Body Condition Score (BCS)] and origin of the carabaos were recorded. The parasites identified were Fasciola gigantica and Paramphistomum cervi. The study showed a prevalence of 50.81% for F. gigantica, 4.31% for P. cervi and 32.11% for coinfection. was more prevalent in female carabaos (57.80%), carabaos more than three years of age (58.41%), >325kg bodyweight (60.36%) and higher than three body condition score (59.09%). Paramphistomum was common in female carabaos (51.37%), carabaos less than or equal to three years of age (46.82%), ≤325kg bodyweight (52.59%) and less than or equal to three (≤3) body condition score (49.64%). Carabaos originating from Leyte have a higher infection rate to Fasciola (53.30%) and Paramphistomum (46.70%) compared to carabaos , supplied by other provinces. Logistic regression modeling indicates that male carabaos are a protective factor (OR 0.59) against Paramphistomum infection while carabaos within Leyte have a greater likelihood of being infected with both parasites (OR 4.27 to 4.57). Pearson’s Correlation Coefficient (r-value) showed a strong and positive result (r=0.997**) that the likelihood of Fasciola and Paramphistomum co-exist (co-infection) together is high. A high prevalence rate of fluke infection has been recorded in carabaos admitted for slaughter implying, that most of the backyard carabao raisers are not practicing sound deworming, pasture and grazing management and proper deworming protocol. To prevent and control flukes and improve production and health of carabaos, the above-mentioned factors must first be considered.